The Law of God: Exploring God and Civilization - Zijlstra, Onno; Vos, Pieter (Studies in Reformed Theology, 2014)
In today's society, religion as adherence to 'the law of God' is often considered inherently violent and a threat to civilization. This volume contains theological and philosophical explorations of clashes as well as disclosures of God and civilization